Imaging Features of Hepatocellular Carcinoma With Bile Duct Tumor Thrombus: A Multicenter Study - Wu, Jun-Yi; Huang, Li-Ming; Bai, Yan-Nan; Wu, Jia-Yi; Wei, Yong-Gang; Zhang, Zhi-Bo; Yan, Mao-Lin (Frontiers in Oncology, 2021)
Objectives There are still challenging problems in diagnosis of hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT) before operation. This study aimed to analyze the imaging features of HCC with B1–B3 BDTT. Materials and Methods The clinicopathological data and imaging findings of 30 HCC patients with B1–B3 BDTT from three high-volume institutions were retrospectively reviewed. A total of 631 patients without BDTT who were randomly collected from each of the enrolled centers were recorded as the control group to analyze the differences in clinicopathological characteristics and imaging features between the two groups. A total of 453 HCC patients who underwent surgical treatment in the three institutions from January 2020 to December 2020 were collected for a blinded reading test as the validation group. Results HCC patients with B1–B3 BDTT had more advanced tumor stages and adverse clinicopathological features. HCC lesions were detected in all patients, and intrahepatic bile duct dilation was observed in 28 (93.3%) patients with B1–B3 BDTT and 9 (1.43%) patients in HCC without BDTT. The intrahepatic bile duct dilation showed no enhancement at hepatic arterial phase (HAP) and no progressively delayed enhancement at portal venous phase (PVP), but it was more obvious at PVP on CT. In the reports of the 30 HCC patients with B1–B3 BDTT generated for the image when the scan was done, BDTT was observed in all 13 B3 patients and 3 of 12 B2 patients, but none of the 5 B1 patients. Fourteen patients were misdiagnosed before surgery. However, when using intrahepatic bile duct dilation in HCC patients as a potential biomarker for BDTT diagnosis, the sensitivity and specificity for BDTT diagnosis were 93.33% and 98.57%, respectively. The blinded reading test showed that intrahepatic bile duct dilation in CT and MRI scans could be for separating HCC patients with B1–B3 BDTT from HCC patients without BDTT. Conclusions The HCC lesions and intrahepatic bile duct dilation on CT or MRI scans are imaging features of HCC with BDTT, which might facilitate the early diagnosis of B1–B3 BDTT.